The feature of neoconservative foreign policy: the case of the USA - Alexey A. Bezrukov (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2016)
The article deals with the influence of neo-conservatism on the foreign policy strategy of the USA. The author shows that despite obvious failures neoconservative paradigm is still the basement of US foreign policy.